Fresno County Bar Association Law Day Luncheon: Judge Robert Coyle Speaker - Watkins, Howard::::::::: (1986)
Pro Bono Coordinator Carmen Romero speaking at lectern; Thomas Richey, Catherine Golden-Taylor, Judge Robert Coyle and Faye Coyle